Inside Cover: Molecular Basis for Two Stereoselective Diels–Alderases that Produce Decalin Skeletons (Angew. Chem. Int. Ed. 41/2021). Issue 41 (9th August 2021) - Fujiyama, Keisuke; Kato, Naoki; Re, Suyong; Kinugasa, Kiyomi; Watanabe, Kohei; Takita, Ryo; Nogawa, Toshihiko; Hino, Tomoya; Osada, Hiroyuki; Sugita, Yuji; Takahashi, Shunji; Nagano, Shingo
Abstract : A linear hydrocarbon chain containing a diene and a dienophile is folded and transformed into a decalin scaffold by intramolecular [4+2] cycloaddition. The substrates are folded oppositely but bind in the same orientation to the pockets of a pair of Diels–Alderases to yield enantiomeric decalin skeletons, as reported by Naoki Kato, Shunji Takahashi, Shingo Nagano, and co‐workers in their Research Article on page 22401 .